Revolution and Economic Transition: The Iranian Experience By Hooshang Amirahmadi. Albany, NY: State University of New York Press, 1990, 384pp. (American Journal of Islam and Society, 1991)
In this book, the author offers an empirical and theoretical analysis ofthe relationship between the Iranian Islamic revolution and the performanceof the Iranian economy. The book in divided into three main chapters plusan introduction and a conclusion.In the introduction, the author gives a profound analysis of the prerevolutionaryperiod with a special emphasis on the Shah's open-door economicpolicies which led to rapid and uneven economic growth and eventually increasedIran's economic dependence on the capitalist world. The author alsoanalyzes the emerging political, cultural, and social ideologies in the Iraniansociety which set the stage for revolution. The proclaimed aims of the revolutionwere listed as achieving economic development, sovereignty, and justice. Thesewere subsequently transformed into an Islamic vision as reflected in the constitutionand the first socioeconomic plan of the Islamic Republic.In the second chapter, the forces influencing the postrevolutionary economyare pointed out. The major force was the war which erupted with Iraq inthe early 1980s. Apart from the destruction and loss of life, the war hadan overwhelmingly negative and permanent impact on the economy ...